Visual effects of the luminance surrounding a computer display. - Sheedy JE; Smith R; Hayes J (Ergonomics, 2005)
The luminance surrounding a computer display can potentially reduce visibility of the display (disability glare), result in sensations of discomfort (discomfort glare) and result in transient adaptation effects from fixating back and forth between the two luminance levels. The study objective was to measure the effects of surround luminance levels upon these functions in younger and older adults to determine recommended surround luminance levels. The younger age group comprised 20 subjects (mean age 27.9 years, range 23 - 39) and the older group 17 subjects (mean age 55.5 years, range 47 - 63). The central task was presented with luminance of 91 cd/M 2 , tested surround luminance levels were 1.4, 2.4, 8.9, 25.5, 50, 91, 175, 317, and 600 cd/M 2 . Disability glare was tested with low contrast (20%) visual acuity charts, transient adaptation was tested with a task that required regular fixation between the two luminance levels, discomfort was measured with a questionnaire after reading stories with different surround luminance levels, and preferred luminance was measured by method of adjustment. The surround luminance significantly affected transient adaptation ( p